The Effect of The Project Based Learning (PJBL) Model on Poetry Writing Skills With The Help of Image Media in The Fourth Grade of SD Negeri Mekarsari 5 - Heri Agus Wijaya; Fahrurrozi Fahrurrozi; Nidya Chandra Muji Utami (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to determine the effect of the Project-Based Learning (PjBL) model on the poetry writing skills of fourth-grade elementary school students. The background of this study is the low ability to write poetry caused by conventional learning approaches and the lack of use of visual media. The method used is a pseudo-experiment with a one-group pretest-posttest design. The subjects consisted of 30 fourth-grade SD Negeri Mekarsari 5 students who were given learning using the pjbl model assisted by Image media during seven meetings. The main instrument is a test of poetry writing skills assessed based on five aspects: diction, language style, rhyme, suitability of content and theme, and the meaning of poetry. The analysis showed a significant increase in poetry writing skills scores after applying the PjBL model. ANOVA test showed that the PjBL model significantly affects learning outcomes (F = 55,473; p < 0.001), and there is interaction with the initial skills of learners. These findings prove that the PjBL model effectively improves poetry writing skills and can be an alternative to creative learning in elementary school.